1997
DOI: 10.1677/joe.0.1540155
|View full text |Cite
|
Sign up to set email alerts
|

Tri-iodothyronine increases insulin-like growth factor binding protein-4 expression in rat hepatocytes

Abstract: Previous in vivo studies demonstrated significant variations in insulin-like growth factor binding protein-1 (IGFBP-1), IGFBP-2 and IGFBP-4 hepatic mRNAs and/or serum levels depending on the rat thyroid status. In this study we employed cultured hepatocytes from adult rats to demonstrate a possible direct regulation of these genes by tri-iodothyronine (T3). Northern blot analysis revealed that IGFBP-1 and -4 messages were clearly expressed, whereas IGFBP-2 signal was barely detectable. No significant effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
7
22
0
Order By: Relevance
“…A similar T 3 -increased IGFBP-4 expression has been recently reported in cultured rat hepatocytes and is consistent with in vivo experiments demonstrating an increase in serum IGFBP-4 levels in T 3 -treated rats (36). In addition, previous studies showed the specific stimulation of IGFBP-4 expression by T 3 and/or RA in human breast cancer cell lines (49) and mouse osteoblasts (35).…”
Section: Discussionsupporting
confidence: 90%
“…A similar T 3 -increased IGFBP-4 expression has been recently reported in cultured rat hepatocytes and is consistent with in vivo experiments demonstrating an increase in serum IGFBP-4 levels in T 3 -treated rats (36). In addition, previous studies showed the specific stimulation of IGFBP-4 expression by T 3 and/or RA in human breast cancer cell lines (49) and mouse osteoblasts (35).…”
Section: Discussionsupporting
confidence: 90%
“…We have recently demonstrated a tri-iodothyronine (T 3 )-induced increase in IGFBP-4 expression in a rat hepatocyte model, in total agreement with the in vivo effects of thyroid hormone withdrawal from or administration to the rats (Demori et al 1997). In the same experiments, we were unable to obtain evidence of an effect of T 3 on IGFBP-2 expression, because of the barely detectable level of IGFBP-2 message in cultured hepatocytes from adult rats.…”
Section: Introductionmentioning
confidence: 55%
“…75 mM, FFAs) for different periods of time (1, 3, and 6 h). After choosing the optimal conditions of exposure to FFAs, FFA-treated hepatocytes were incubated in the absence (FFAs) or in the presence of T 2 or T 3 at different concentrations (nominal concentrations ranging from 10 K7 to 10 K5 M) for 24 h (Demori et al 1997). Both iodothyronines were added from stock solutions (10 K3 M in 50 mM NaOH).…”
Section: Cell Culturementioning
confidence: 99%